2017
DOI: 10.3390/nano7020047
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of New Hydrophobic Silica Nanoparticles on the Surface Properties of the Films Obtained from Bilayer Hybrids

Abstract: Ultra-hydrophobic bilayer coatings on a glass surface were fabricated by sol–gel process using hexadecyltrimethoxysilane (C16TMS) and tetramethoxysilane (TMOS) (1:4 molar ratio) as precursors. After coating, silica nanoparticles (SiO2 NPs) functionalized with different mono-alkoxy derivatives (methoxytrimethylsilane, TMeMS; ethoxydimethylvinylsilane, DMeVES; ethoxydimethylphenylsilane, DMePhES; and methoxydimethyloctylsilane, DMeC8MS) were added, assuring the microscale roughness on the glass surface. Influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 31 publications
3
24
0
Order By: Relevance
“…Generally, the hydrodynamic size obtained by DLS in aqueous suspension are large since the thickness of the solvation layer and nanoparticle aggregation [47]. Similar observations were reported earlier [48,49].…”
Section: Particle Size and Zeta Potential Measurementssupporting
confidence: 83%
“…Generally, the hydrodynamic size obtained by DLS in aqueous suspension are large since the thickness of the solvation layer and nanoparticle aggregation [47]. Similar observations were reported earlier [48,49].…”
Section: Particle Size and Zeta Potential Measurementssupporting
confidence: 83%
“…However, on account of the high surface energy of nanoparticles and the fact that they usually do not contain active functional groups, the dispersion of nanoparticles in polymers is very poor, thus leading to weak reinforcing effects [11,12]. A number of studies have shown that most properties of composite materials depend on the nanoparticles dispersion in polymer matrix and their interfacial interaction [13][14][15]. Therefore, there are numerous examples have been proposed for improving the dispersion of nanoparticles in polymer matrix thus improving the interfacial interactions by grafting or surface modified materials on the surface of nanoparticles for functionalization [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…This roughness and height up diameters of the nanocomposite, can be attributed to linkage of different synthesized chains of heterocyclic thiadiazole polymers, with surface of grafting silica to formation nanocomposite [21]. It is strongly dependent on the growing conditions and the surface processing methodologies [22]. Particles size distribution of samples display that the particles of modified silica in Figure 16.…”
Section: Atomic Forces Microscopy Of Nanocomposites (Afm)mentioning
confidence: 94%